(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
An algorithm has been developed to optimize the technological process of kaolin enrichment, which is based on the theory of fuzzy sets, allowing objects to be evaluated according to their degree of belonging to a certain class and the gradient method. The dependences of the gradient values and the redistribution of weights on the initial values, as well as on the degree of correlation of the distributions of these weights, are considered.